Pengaruh pemberian sari umbi bit (beta vulgaris) terhadap kadar hemoglobin dan performa atlet sepak bola - Dieny, Fillah Fithra; Fitranti, Deny Yudi; Panunggal, Binar; Safitri, Iqlima (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background: Nutritional factors in athletes were very influential to lead achievement. Giving special food or drink is also important to improve VO2max. One of the substances that can optimized the levels of VO2max is the content of nitrates in foodstuffs. The beetroot is one source of food with high nitrate content.Objective: This study aimed to analyze the effect of bit extract (beta vulgaris) on Hb Levels and performance among football athleteMethods: Design of quasi experimental research with pretest-post test control group approach, conducted on 18 athletes of UNNES Football Club aged 18-22 years. The treatment of beetroot juice was given for 7 days, consist of P200 treatment group consumed 200 ml, P300 was given 300 ml, while control consumed 300 ml of syrup with the same color with beet extract. Athlete’s performance was obtained with VO2max levels. VO2max measurements were taken twice using MFT (multistage fitness test) on day 1 before intervention and day 7 after intervention. Confounding variables were energy intake, macronutrient intake, iron intake, vitamin C intake, and smoking habits. The analysis using by paired-t-test, kruskal wallis, and one way anova.Result: Most subjects had intake (energy, carbohydrate, fat, protein, iron and vitamin C) less categories. Most of the subjects had a good category VO2 Max and were excellent, as well as not anemic. There was no significant effect of treatment on VO2 Max and Hb level (p <0.05), but the increase in VO2 Max was greater in group P 300 than in group P 200 and control. Hb levels of subjects after intervention decreased, but still relatively normal levels. Conclusions: There was no significant effect of giving beetroot juice on VO2 Max and Hb levels, but the increase in VO2 Max in group P 300 was higher than in P group of 200 and control group.